2020
DOI: 10.1177/1082013220973815
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of flaxseed milk fermentation for the production of functional peptides and estimation of their bioactivities

Abstract: Bioactive peptides are protein fragments which have a positive impact on the functions and conditions of living organisms. Apart from other animal and plant sources flaxseed is an excellent source of bioactive peptides. In recent years, fermentation has been explored as effective way for bioactive peptides generation. Hence, the present study has been carried out to evaluate an indigenous Lactobacillus plantarum strain NCDC 374 for fermentation and peptides generation in flaxseed milk. Optimization of fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Sharma et al . (2020) looked at the development of Lactobacillus plantarum strain NCDC 374 on a protein‐rich flaxseed medium. In contrast to our findings, they found that L. plantarum grew slowly in a protein‐rich flaxseed medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma et al . (2020) looked at the development of Lactobacillus plantarum strain NCDC 374 on a protein‐rich flaxseed medium. In contrast to our findings, they found that L. plantarum grew slowly in a protein‐rich flaxseed medium.…”
Section: Resultsmentioning
confidence: 99%
“…There is no similar research on the effect of flaxseed lignan on the development of bacteria in milk medium. Sharma et al (2020) looked at the development of Lactobacillus plantarum strain NCDC 374 on a protein-rich flaxseed medium. In contrast to our findings, they found that L. plantarum grew slowly in a protein-rich flaxseed medium.…”
Section: Lactiplantibacillus Plantarummentioning
confidence: 99%
“…Antioxidant activity was determined by checking the DPPH inhibition (%). DPPH inhibition was checked as per the method suggested by Sharma et al (2021) by using the formula DPPH radical scavenging activity%=A0Anormals/A0×100 where A 0 is the absorbance of control at 517 nm and A S is the absorbance of sample at 517 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidant activity was determined by checking the DPPH inhibition (%). DPPH inhibition was checked as per the method suggested by Sharma et al (2021) by using the formula…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…These properties were attributed to the presence of GABA and other compounds such as polyphenols and lactic acid [ 73 , 108 , 109 , 110 ]. In contrast, other studies have demonstrated the release of bioactive peptides after fermentation from proteins in soy [ 100 , 111 ], flaxseed [ 112 ], coconut [ 113 ], and oat [ 114 ] beverages, which presented antioxidant and antimicrobial properties as well as ACE inhibition [ 91 , 100 , 113 , 114 ].…”
Section: Impact Of Fermentation On Nutritional Composition Sensory Pr...mentioning
confidence: 99%